O ensino da temática feridas no Curso de Graduação em Enfermagem da Universidade Federal da Paraíba - Santos, Antonio Adriano Rodrigues dos (2012)
This dissertation is based on teaching under the thematic of injuries in a nursing course. It was a documental study, descriptive, exploratory and of qualitative nature, carried out at the campus I of UFPB (João Pessoa - PB). This study is aimed at analyzing the teaching of the subject injuries in the undergraduate course of nursing at UFPB. The collection of data was divided into two stages The first stage focused on the apprehension and analyzing the course plans of the compulsory subjects of the undergraduate Nursing course (Bachelorhood). Secondly, a taped interview was conducted with the teachers, through a semi-structured guide and was focused on the identification of pedagogical approaches, teaching strategies, the career, the teacher-student teaching relationship, the teaching techniques used in order to motivate the study of the topic in question and the difficulties encountered in teaching-learning process. The Nursing Undergraduate course at UFPB is made up of 54 course plans, but we only obtained 48 course plans, because due to administrative problems 06 were not provided. In obedience to inclusion criteria, the first stage sample was made up of 10 subjects. In the second stage, the population consisted of all the teachers responsible for teaching the subjects identified in the first stage, a total of 37 teachers. After the definition and application of the inclusion criteria, the sample consisted of 18 teachers. Data collection was conducted between the months of August and December 2011. The data was subjected to Bardin content analysis technique. This research gave us the opportunity of evaluating how the subject theme injuries is been taught at UFPB, either from a more traditional or a more problematical approach. Academic training should be able to provide the students with sufficient knowledge for their professional life as to caring for patients with injury. This aspect is possible from a consistent and higher education which provides the student with the theoretical support which is essential for their proper professional performance, which of the teachers better preparation and pedagogical theory for teaching the subject injuries. Several key points were observed, such as the approaches, strategies and teaching techniques which might influence the idea of what is best thing for nurse training in relation to the theme injuries. It was concluded that more research is still needed on the subject, as well as a further curricula adaptation so that this subject theme might be addressed more effectively during the undergraduate course in Nursing at UFPB.